Conceptualization of legal terminology: the need for a transparent terminological approach - V. V. Lazariev (Law and Safety)
The article is devoted to the study of the peculiarities of the conceptualization of legal terminology. It has been emphasized that legal concepts are important for the functioning of legal institutions. It has been noted that most of the legal terms aimed at unambiguous and consistent interpretation of legal texts are established in various legal documents. The boundaries of most subject areas are unclear, and their use in different areas of law may lead to the application of different criteria to establish the essence of the term. Attention is drawn to the fact that terminological work traditionally focuses on the organization of concepts and lexical items in a specialized field, in which each term is one concept, and each concept is denoted by one term. The definition of a particular area of law and terms related to that area includes the establishment of both terminological and conceptual boundaries, which allows clear and unambiguous use of the relevant categories. A clear approach to understanding the term contributes to the quality of legislation that affects the stability of state life. It is emphasized that ambiguous terms are used in modern legislation. Given the foreign experience in the context of European Union law, the timing of interdisciplinary concepts seems more appropriate due to the complex relationship between the national law of the Member States and the law of the European Union. Emphasis is placed on interdisciplinary concepts, i.e. concepts or institutions that arise in more than one legal field. More specifically, such concepts may apply to both the national legal system and the law of the European Union. Although the same term is used to denote an interdisciplinary concept, its conceptualization may differ in various areas of law and different legal systems, which may adversely affect the case because there will be no common approach to understanding the term. It is noted that the study of legal terminology should focus on the elements of the legal solution of the real problem.